Hierarchical structures of machines for packing of viscous and plastic foodstuff and their synthesis - Gavva, Oleksandr M.; Tokarchuk, Serhii; Kokhan, Olena (My University, 2015)
Continuous expansion of the range of viscous and plastic products, use of different types of a retail container, search of the functional modules and communications in between cause need of creation of effective methodology of the description and an assessment of structure of packing machines according to different characteristics. Application of hierarchical structure of packing machines allows to research options of their configuration, both at the level of units of the functional modules, and at the level of the machine in general. The methodology of SADT ("Structured Analysis & Design Technique") which allowed constructing three levels conceptual model of the machine is applied to effective analysis of structure packing machines: the functional, functional - structural and structural.
Keywords: plastic food packaging; packaging machine; пакування пластикових харчових продуктів; пакувальна машина; SADT; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра мехатроніки та пакувальної техніки; кафедра технології хлібопекарських і кондитерських виробів